2014
DOI: 10.1016/j.jped.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of and factors associated with vascular complications after pediatric liver transplantation

Abstract: the choice of treatment depends on the timing of diagnosis; however, in this study, surgical revision or correction produced worse outcomes than percutaneous angioplasty. The reduction of risk factors and early detection of vascular complications are key elements to a successful transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 28 publications
3
52
0
1
Order By: Relevance
“…They also found those patients who developed vascular complications had younger donors than those who did not, though the difference was not statistically significant (median age 5 vs 12, P = .084). Because of these findings, they suggest that WL grafts from small young donors may have an innate predisposition to developing post‐operative HAT, even when carefully size matched to recipient weight . In our study, we found that patients who developed HAT following WL had significantly younger donors (Table ).…”
Section: Discussionsupporting
confidence: 91%
“…They also found those patients who developed vascular complications had younger donors than those who did not, though the difference was not statistically significant (median age 5 vs 12, P = .084). Because of these findings, they suggest that WL grafts from small young donors may have an innate predisposition to developing post‐operative HAT, even when carefully size matched to recipient weight . In our study, we found that patients who developed HAT following WL had significantly younger donors (Table ).…”
Section: Discussionsupporting
confidence: 91%
“…Portal vein hypoplasia is also one of the main risk factors for vascular complications following pediatric liver transplantation, especially in children with biliary atresia . An intraoperative finding of portal diameter ≤3 mm was a statistically significant predictor of vascular complications in the post‐operative period . Previous studies have reported that a hypercoagulable state following pediatric LRDLT is another important risk factor for vascular thrombosis.…”
Section: Discussionmentioning
confidence: 94%
“…[8] In LT recipients, it has been reported that the occurrence rate of PVT was more in patients with HCC, autoimmune chronic active hepatitis, cryptogenic cirrhosis, alcoholic liver disease, or patients with previous treatment of portal hypertension-related bleeding. [8] Orlandini et al [9] found that the following factors, including portal vein diameter ≤3 mm, donor-to-recipient body weight ratio, prolonged ischemic time, and use of arterial grafts, associated with vascular complications in patients undergoing orthotopic liver transplantation. The incidence of vascular complications in patients with portal vein (PV) diameter >3 mm or ≤3 mm are about 20% or 50%, respectively, after 10 years of orthotopic liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of vascular complications in patients with portal vein (PV) diameter >3 mm or ≤3 mm are about 20% or 50%, respectively, after 10 years of orthotopic liver transplantation. [9] Although the survival rates between patients with PVT and patients without PVT had no difference, Neto et al [3] proved that the use of vascular grafts in living donor liver transplantation was an independent risk factor for the occurrence of PVT. The other common factors include excessive length of portal vein, hypercoagulability, thrombus history, portal manipulation, and caliber discrepancies between the donor and recipient veins.…”
Section: Discussionmentioning
confidence: 99%